Why did ancient civilizations fail? - Johnson, Scott A. J., 1983-, author.
1 online resource
Keywords: "Ideas abound as to why certain complex societies collapsed in the past--environmental change, subsistence failure, fluctuating social structure, lack of adaptability. Why Did Ancient Civilizations Fail? evaluates the current theories in this important topic and discusses why they offer only partial explanations of the failure of past civilizations. This engaging volume offers a new theory of collapse, that of social hubris. Through an examination of Mesopotamian, Egyptian, Roman, Maya, Inca, and Aztec societies, Johnson persuasively argues that hubris has blinded many ancient peoples to evidence that would allow them to adapt, and that this has implications for contemporary societies. Comprehensive and well-written, this volume serves as an ideal text for undergraduate courses on ancient complex societies, as well as appealing to the scholar interested in societal collapse"--Provided by publisher.